Implementation of the Quick Response Code Indonesia Standard (QRIS) Payment System as a Medium for Digital Financial Literacy Education in Coffee Shops - M. Zainuri; Ruski (Global Action and Education for Society, 2025)
Digital transformation in payment systems is an important strategy in driving the efficiency of economic transactions, especially in the micro, small, and medium enterprises (MSMEs) sector. One of the payment system innovations that is growing rapidly in Indonesia is the Quick Response Code Indonesian Standard (QRIS), which is implemented by Bank Indonesia to unify various digital payment systems into one national standard. This study aims to analyze the implementation of QRIS in payment transactions for Coffee Shop business actors in Bangkalan. This study uses a descriptive qualitative method with a case study approach to five Coffee Shop business actors in Bangkalan who use QRIS as their main payment method. The results of the study show that the use of QRIS provides significant benefits such as ease of transactions, time efficiency, increased turnover, and transaction security. However, there are obstacles faced by business actors such as technical disruptions, dependence on a stable internet connection, and lack of technical education for business actors and consumers. This study recommends increasing digital literacy education, strengthening internet infrastructure, and technical support from the government and payment system service providers to support the optimization of QRIS implementation in the MSME sector, especially in the Coffee Shop industry.